Critical care nursing of older adults : best practices - Foreman, Marquis D.; Milisen, Koen; Fulmer, Terry T. (Springer Pub. Co., 2010)
In increasing numbers, geriatric patients are being treated in intensive and critical care, as well as by trauma and emergency departments. This book is an evidence-based, best-practices guide that directs the bedside care of critically ill elders by practicing ICU nurses in an area where the care needs and issues differ from those of younger adults. The elderly present special clinical challenges, since concomitant diseases complicate their management. The clinical section discusses major disorders arising in elder care, explains how to isolate the problem, and offers evidence-based practice.